Design and derivation of the Austrian Prehospital Stroke Scale (APSS) to predict severe stroke with large vessel occlusion - Krebs, Stefan; Roth, Dominik; Knoflach, Michael; Baubin, Michael; Lang, Wilfried; Beisteiner, Roland; Purrucker, Jan; Poli, Sven; Sykora, Marek (Prehospital emergency care, 2021)
Objectives: Prediction of large vessel occlusion (LVO) is highly relevant for accurate prehospital transportation triage. The Austrian Prehospital Stroke Scale (APSS) score for LVO prediction was developed using critical synthesis of previously published LVO-scores. The aim of this study was to investigate the accuracy of the APSS and compare it to other LVO-scores. Methods: APSS consists of 5 items: “facial palsy,” “motor arm,” “language,” “motor leg” and “gaze deviation.” The score ranges from 0 to 9 points. Data from 741 consecutive stroke patients with acute vessel imaging admitted to an independent comprehensive stroke center was used to test the predictive performance of the APSS in context of other LVO-scores (CPSS, FAST-ED, G-FAST, sNIHSS-EMS and RACE). Results: In the prediction of treatable LVO the APSS showed the highest area under the curve (0.834) with significant difference to CPSS (p = 0.010) and G-FAST (p = 0.006) and showed highest sensitivity (69%) as compared to other LVO scores. Specificity (85%), positive predictive value (75%), negative predictive value (81%) and accuracy (79%) were comparable to other LVO scores. Receiver operating curve analysis revealed an optimal cutoff for LVO prediction at APSS equal to 4 points. Conclusions: The easy assessable 5-item APSS score tended to outperform other LVO scores. Real-life prospective evaluation in prehospital setting is ongoing.